Amount and distribution of welding fume lung contaminants among arc welders. - Kalliomäki, Pirkko-Liisa; Alanko, Kristiina; Korhonen, Olli; Mattsson, Tor; Vääränen, Vesa; Koponen, Matti (Scandinavian Journal of Work, Environment & Health, 1978)
The amount and distribution of the welding fume lung contaminants was measured in 44 arc welders from two shipyards. The measurement was made from the determination of the permanent field after the subject was magnetized in a low external magnetic field, the values being used for the calculation of the amount of contaminants in the lungs. Less than 4 mg of dust was found in the lungs of nonexposed controls. In the shipyard welder's lungs, after two years of exposure, on the average 7 mg (range 4-15) of welding dust was observed. After a continuous exposure of about 18 years the amounts were 200 mg (range 30-1,500) in shipyard A and 700 mg (150-2,000) in shipyard B, respectively. On the basis of data obtained from retired welders, the clearance rate of 45% in welders from shipyard A and 18% in shipyard B were calculated, the latter figure being probably more accurate. The distribution of contaminants was 52% in the right and 48% in the left lung. The radiological findings correlated well with the amounts of welding fume contaminants measured with the magnetic method.
Keywords: arc welder; lung; lung contaminant; lung contaminant distribution; lung retention; pulmonary clearance; shipyard arc welder; siderosis; welder; welding fume; welding fume lung contaminant